If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13 = a + 3 Reorder the terms: -13 = 3 + a Solving -13 = 3 + a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. -13 + -1a = 3 + a + -1a Combine like terms: a + -1a = 0 -13 + -1a = 3 + 0 -13 + -1a = 3 Add '13' to each side of the equation. -13 + 13 + -1a = 3 + 13 Combine like terms: -13 + 13 = 0 0 + -1a = 3 + 13 -1a = 3 + 13 Combine like terms: 3 + 13 = 16 -1a = 16 Divide each side by '-1'. a = -16 Simplifying a = -16
| x^2+8x^2=-15x | | 9c=27 | | n/-4=11 | | 9c=20 | | 30(20)-10(1x)=15(1x) | | (-2-6i)-(4-6i)=0 | | (n)(n)= | | a^9/a^5 | | 2(y-9)=3y-4 | | -n^2-7n-10= | | p-11=-11 | | 38+7k=8 | | 4x^2+44x+121=0 | | 3(5-10)=x-4 | | 5=30b | | 12=-3(2x+2) | | (A+b)x=a+b | | 3(x-9)+4=8(4-8x) | | q^2-6q+35= | | -6x+17=3(1+x)-9x | | 6=4y-3y+2 | | 2k+7k=45 | | 3u^2+16u+5=0 | | 3+v=1 | | 79(y-50)=y-25 | | (6-3i)+(5+4i)=0 | | 4x^2+12x-72= | | 2z+2z-3z=12 | | 12=-3(2x-2) | | 49x^2+49x-8=0 | | 2x^3-12x^2=14x | | 42x-12=-10-7x |